The Relationship between Economic Level and Political Participation in the North Sumatra Governor Election in Neighborhood V, Bagan Deli Village, Medan Belawan District - Steven Leonardo Silalahi (Trigin Publisher, 2022)
Political participation is one aspect that affects the achievement of a democratic government. One of the factors that influence political participation is the economic level. Thus, the high and low level of the economy will affect the level of one's political participation. To determine whether there is a relationship between economic level and political participation, a quantitative approach is used through correlation coefficient tests and simple regression analysis. Based on the results of calculations through the correlation coefficient test shows that the independent variable, namely the economic level (X) and the dependent variable, namely political participation (Y) has a positive relationship with an r value of 0.214. This value indicates a positive relationship between the two variables with a low level of closeness. From the results of simple regression analysis, the equation Y = 9.900 + 0.153X with the value of Fcount is 4.319 and Ftable is 3.94. These results indicate that the regression analysis is significant with a statistical value of Fcount > Ftable, which means Ho is rejected and Ha is accepted, that is, there is a significant positive relationship between economic level and political participation. Thus, every increase in the value of variable X, namely the economic level by 1 time, political participation will increase by 0.153 times. So it can be concluded that the higher the economic level, the higher the level of political participation of a person, and vice versa. Meanwhile, through the coefficient of determination test obtained a value of 0.46 which means that the economic level has an influence of 46% on political participation. The rest,